MODEL SURAMADU DENGAN INTEGRASI NEARPOD DAN ESTAFET NUSANTARA: UPAYA PENINGKATAN KETERAMPILAN BERPIKIR KREATIF DAN KOLABORATIF - Putri Elok Maufikhoh; Diani Ayu Pratiwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study examines how the use of the SURAMADU model and Nearpod media combined with the Nusantara relay game in Pancasila Education lessons can be a solution to overcome students' low ability to think creatively and collaboratively. This condition arises due to the use of learning models and media that are not yet creative and varied. This study was conducted in four meetings in class V of Sungai Tabuk Keramat 2 Elementary School by combining qualitative and quantitative data. The results showed that students' creative thinking skills increased from 12% (less skilled) at the first meeting to 88% (very skilled) at the fourth meeting. Likewise with collaborative skills, which increased from 46% (quite skilled) to 100% (very skilled) at the last meeting. This proves that the SURAMADU model and Nearpod media are effective in improving the quality of learning and can be an innovative method choice in Education.